Politik Hukum Mahkamah Konstitusi dalam Membatalkan Konsep Empat Pilar sebagai Upaya Mendudukkan Pancasila Sebagai Dasar Negara - Udiyo Basuki (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2015)
This paper is the result of research that has been overshadowed by the studyauthors theoretical and empirical, that Pancasila is the basis of the state and a source oflaw as stated in the Preamble to the Constitution of the Republic of Indonesia Year1945 fourth paragraph. In the system of legislation, Pancasila is the basic norm(staatsfundamental), successive later verfassungnorm 1945, grundgezetznorm or MPRdecrees, as well as gezetznorm or the Act. But in reality, the Pancasila likened hisposition and aligned with the 1945 Constitution, the Unitary Republic of Indonesia,Unity which was then called the "Four Pillars of Nation and State". Results penilitianfound that the political law of the Constitutional Court makes a decision positiveLegislature in Constitutional Court Decision No. 100 / PUU-XI / 2012, is part ofthe authority of the Constitutional Court that has 4 (four) authority and one (1) theobligations as set forth in Article 24C paragraph (1) and (2) 1945. In addition to astate institution guardian of democracy (the guardian of democracy) the ConstitutionalCourt as well as the protector of the state and legal sources. To support the political law,the Constitutional Court did various things, including the technical organization of thetrial. Position Pancasila as the state after the aborted phrase "four pillars of the stateand nation is" back Pancasila as the state not as the pillars of the nation as stated inthe fourth paragraph of the Preamble of the 1945 Constitution